Ketogenic therapy:the experience of adult brain tumour patients supported by Matthews Friends. (31st January 2018) - Wood, Susan; Zabilowicz, Catherine; Aldridge, Val; Sheen, Katie; Williams, Emma; Williams, Matthew
Abstract: BACKGROUND: There is increasing interest in ketogenic diet (KD) as an adjuvant to standard care (surgery, chemo-radiation, dexamethasone and anticonvulsant medication) for brain tumour and associated symptom management, within the brain tumour community. Published clinical trial data is extremely limited and there are no NHS clinical services to support KD therapy in this patient group. Since 2011, Matthews Friends has provided charitably funded* specialist dietetic support to over 50 adults from across the UK and Ireland, requesting help to explore KD therapy as a component of their brain tumour management. These self-selected cases vary considerably in terms of age, tumour type, stage of treatment and degree of quality of life impairment. However recurring themes have emerged from these cases, in relation to the practical, physical and emotional experience of implementing KD as therapy. METHOD: A questionnaire was devised and sent to twenty-three patients on KD therapy. Fourteen (60%) were returned. Results of this survey will be presented in relation to: The experience of starting ketogenic therapy; the ease of adaption to the diet change, the impact of the monitoring process and the effect of the lifestyle change on families. How this has been supported by their clinical team and during hospital admissions. The physical effects of the therapy in relation to weight, gastrointestinal function, seizures, headaches, vision, speech, fatigue and coordination. The effects on thoughts, feelings and their ability to function day to day. CONCLUSION: All fourteen patients were able to implement and sustain KD for between 8months-4 years, reporting varying aspects of personal benefit from this. * Astro Brain Tumour Fund and Matthew's Friends Charities